Impact of secondary ice production on thunderstorm electrification under different aerosol conditions - S. Huang; J. Yang; J. Yang; J. Li; Q. Chen; Q. Zhang; F. Guo (Atmospheric Chemistry and Physics)
Aerosol and secondary ice production (SIP) processes are both vital to charge separation in thunderstorms, but the relative importance of different SIP processes to electrification under different aerosol conditions is not well understood. In this study, using the Weather Research and Forecasting (WRF) model, we investigate the role of four different SIP processes in charge separation with different aerosol concentrations, including the rime splintering (RS), the ice–ice collisional (IC) breakup, shattering of freezing drops (SD), and sublimational breakup (SK). It is found that as the aerosol concentration increases, more but smaller cloud droplets can be lofted to mixed-phase regions. The warm-rain process is suppressed, and the declined raindrop concentration leads to fewer graupel particles. In a clean environment (aerosol concentration <1000 cm−3), the SD process is the most important to ice production between 0 and −10 °C, while in a polluted environment (aerosol concentration ≥2000 cm−3), the RS process contributes the most between 0 and −10 °C. The IC process is important between −10 and −20 °C. The SIP processes and the increase in aerosol concentration both enhance the noninductive charging rate. However, aerosol and SIP processes have opposite impacts on the charging reversal, which implies they play different roles in controlling the charge structure. In a clean (polluted) environment, the SD (RS) process has the greatest effect on the charge structure. Both the SIP processes and the increase in aerosol concentration enhance the electric field, but the enhancement in the flash rate induced by increasing aerosol concentration is much greater than SIP.